Transcriptome reveals the role of the htpG gene in mediating antibiotic resistance through cell envelope modulation in Vibrio mimicus SCCF01 - Qin, Zhenyang; Peng, Kun; Feng, Yang; Wang, Yilin; Huang, Bowen; Tian, Ziqi; Ouyang, Ping; Huang, Xiaoli; Chen, Defang; Lai, Weimin; Geng, Yi (Frontiers in Microbiology, 2024)
HtpG, a bacterial homolog of the eukaryotic 90kDa heat-shock protein (Hsp90), represents the simplest member of the heat shock protein family. While the significance of Hsp90 in fungal and cancer drug resistance has been confirmed, the role of HtpG in bacterial antibiotic resistance remains largely unexplored. This research aims to investigate the impact of the htpG gene on antibiotic resistance in Vibrio mimicus. Through the creation of htpG gene deletion and complementation strains, we have uncovered the essential role of htpG in regulating the structural integrity of the bacterial cell envelope. Our transcriptomics analysis demonstrates that the deletion of htpG increases the sensitivity of V. mimicus to antimicrobial peptides, primarily due to upregulated lipopolysaccharide synthesis, reduced glycerophospholipid content, and weakened efflux pumps activity. Conversely, reduced sensitivity to β-lactam antibiotics in the ΔhtpG strain results from decreased peptidoglycan synthesis and dysregulated peptidoglycan recycling and regulation. Further exploration of specific pathway components is essential for a comprehensive understanding of htpG-mediated resistance mechanisms, aiding in the development of antimicrobial agents. To our knowledge, this is the first effort to explore the relationship between htpG and drug resistance in bacteria.